2008
DOI: 10.1371/journal.pgen.1000027
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Model Identifies Genetic Modifiers of α-Synuclein Inclusion Formation During Aging

Abstract: Inclusions in the brain containing α-synuclein are the pathological hallmark of Parkinson's disease, but how these inclusions are formed and how this links to disease is poorly understood. We have developed a C. elegans model that makes it possible to monitor, in living animals, the formation of α-synuclein inclusions. In worms of old age, inclusions contain aggregated α- synuclein, resembling a critical pathological feature. We used genome-wide RNA interference to identify processes involved in inclusion form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
425
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 386 publications
(457 citation statements)
references
References 32 publications
21
425
2
1
Order By: Relevance
“…While common phenotyping metrics such as paralysis and lifespan make PD and ALS worm models almost indistinguishable 44,45 , we found that using multiple electrophysiological metrics based on nano-SPEAR recordings allows us to clearly differentiate between the two disease models (Fig. 5b).…”
Section: Phenotyping Neurological Disease Modelsmentioning
confidence: 93%
See 4 more Smart Citations
“…While common phenotyping metrics such as paralysis and lifespan make PD and ALS worm models almost indistinguishable 44,45 , we found that using multiple electrophysiological metrics based on nano-SPEAR recordings allows us to clearly differentiate between the two disease models (Fig. 5b).…”
Section: Phenotyping Neurological Disease Modelsmentioning
confidence: 93%
“…The disease models used were NL5901 (PD) and the ALS strain was obtained from Jiou Wang from the work conducted in Wang, 2009 et al 4 . Specifically these disease models express alpha-synuclein (α-syn) fused to YFP in the body-wall muscles (PD worms) 5 and the G85R mutation of SOD1 fused to YFP in all neurons (ALS worms) 4 . All strains were maintained at approximately 21°C on nematode growth medium (NGM) seeded with OP50, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations